Postgraduate Courses in Pharmaceutical Medicine in Italy - Criscuolo, Domenico (Frontiers in Medicine, 2017)
Italy has a significant tradition of excellence in the area of clinical trials (CTRs): important achievements in the clinical development of rifampicin and adriamycin, the two most famous drugs discovered in the research laboratories of two Italian pharmaceutical companies, paved the way to the establishment of a culture of clinical development, mainly in the areas of antimicrobials and oncology. Despite the fact that now the Italian market of pharmaceuticals is largely dominated by multinational companies with headquarters outside Italy, the contribution of Italian studies to the clinical development of new drugs is still significant. Indeed, it largely exceeds the percentage of Italian inhabitants versus the ones living in the remaining EU countries, as Italy has about 12% of EU population, but has a 17% share of the EU CTRs. Education in Pharmaceutical Medicine is now a must for all professionals interested to work either in pharma companies or in contract research organizations: several Italian universities are offering high quality courses, and in the last 10 years, more than 1,200 professionals received a postgraduate education in pharmaceutical medicine. This result places Italy on top of countries concerned about the professional education of people involved in drug development and will represent an asset for a larger involvement of Italian clinical sites in the global process of clinical research.